Routes africaines vers Le Caire et dynamiques chrétiennes plurielles - Julie Picard (L’Année du Maghreb)
Migratory trans-Saharan routes to Egypt have become more diversified since the end of the 1990s. Refugees from Sudan and from the Horn of Africa (Somalia, Ethiopia, Eritrea) are no longer the only ones to be attracted to this country of the Mashreq. These find refuge in Egypt, while others (students, « adventurers », religious leaders, from Cameroon, DRC or Nigeria) hope to find opportunities to complete their training and continue their journey. However, since the early 2000s, the Egyptian government, the UN institutions in Egypt and the European Union have been involved in the closing of borders and in the creation of a lasting migratory deadlock.The purpose of this article is to explain the settlement processes of African migrants, mostly Christian, to better support the wait. Without legal recognition and integration policy, they access various resources and anchoring means from the bottom, in particular through several Christian missionaries’ institutions, faith-based organizations and for some, through their flexible religious path. Today, Cairo’s urban and religious landscape is thus discretely changed.